1983
DOI: 10.18174/njas.v31i1.16959
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the effect of fat supplementation of concentrates fed to lactating dairy cows. II. Total digestion and energy utilization.

Abstract: For wether sheep given 300 g hay and 800 g concentrates the addition of fat (beef tallow:palm kernel oil 9:1) to concentrates at 7 or 12% tended to decrease crude fibre digestibility and increased crude fat digestibility. For 2 rumen-fistulated cows given concentrates containing 7% fat, or 12% fat free or adsorbed on carrier, and 2 cows with fistulae and reentrant duodenal cannulae given concentrates with 12% fat in rations with hay:concentrate 1:2, there were no significant differences between diets in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…Improved crude fat digestibility with increasing level of oil supplementation occurred because as dietary fat increases, the fraction of endogenous fat excreted in the feces formed a smaller portion of the ingested fat (van der Honing et al . ). Also, Kronfeld et al .…”
Section: Discussionmentioning
confidence: 97%
“…Improved crude fat digestibility with increasing level of oil supplementation occurred because as dietary fat increases, the fraction of endogenous fat excreted in the feces formed a smaller portion of the ingested fat (van der Honing et al . ). Also, Kronfeld et al .…”
Section: Discussionmentioning
confidence: 97%
“…Hay was fed at 6h00 and 15h30; concentrates were offered one hour later. Compo sition of the concentrate mixtures was reported in a previous paper (van der Honing et al, 1983). Animals with only a rumen cannula received all three treatments, ani mals also equipped with duodenal cannulae received treatments C12 and C12C only.…”
Section: Methodsmentioning
confidence: 91%
“…The effect of fat supplementation was studied in dairy cows equipped with rumi nai and duodenal cannulae. With these animals energy balance studies were per formed, the results of which were reported in a previous paper (van der Honing et al, 1983). The effect on rumen fermentation and site of digestion of various dietary components is reported in this paper.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The mixtures were subse quently pelleted. Details on the composition of the concentrates are given in a subsequent paper (van der Honing et al, 1982). The chemical composition of the hay and the concentrates are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%